PCR-based immortalization and screening of hierarchical pools of cDNAs. - D'Esposito, M (1994)
Starting from sequences of at least 60 bp, PCR-based screening has been developed to recover cDNAs from libraries without the necessity for hybridization or extensive DNA extraction steps. The method maintains the indefinite availability of even scarce cDNA libraries and provides an estimate of the relative abundance of the mRNA species. Isolation of a cDNA clone can be done in less than a week. cDNAs were isolated that were cognate for fragments of expressed sequences and for an exon predicted from genomic sequence.